Basic Heading Techniques Training for FIKK UNM Students as the Foundation of Individual Abilities - M. Said Zainuddin; Arifuddin Usman; Ahmad Zakaria; Benny Badaru; Awaluddin Awaluddin (Jurnal Perjuangan dan Pengabdian Masyarakat : JPPM, 2026)
This community service initiative aims to enhance safe and effective fundamental heading skills among FIKK UNM students, serving as a cornerstone for individual soccer proficiency. The program addresses the critical need for technical mastery to mitigate the risk of repetitive subconcussive head injuries by integrating biomechanical principles and neck muscle strengthening protocols. The training is delivered through a systematic progression, transitioning from sensory adaptation to structured and directed static and dynamic techniques. The anticipated outcomes include the attainment of superior technical competence and a comprehensive understanding of FIFA safety protocols (SCAT6/CRT6) as a benchmark for professional conduct on the field. Accurate worthless, easy to read, and concise, followed by up to 5 keywords, separated by semicolons.